The Effect of a Realistic Mathematical Approach on the Mathematical Problem Solving Ability of Class VIII Students of SMP IT Al-Hijrah 2 Deli Serdang - Chintya Rachmawati Putri Sarmi; Asmin (Formosa Journal of Applied Sciences, 2022)
The purpose of this study was to determine the effect of a Realistic Mathematical Approach on Students' Mathematical Problem Solving Ability. This research was conducted at SMP IT Al-Hijrah 2 Deli Serdang for the 2022/2023 academic year. The method used in this study is a quasi-experimental method with a Post-Test Only research design. The research sample consisted of two classes consisting of 21 students in the experimental class and 17 students in the control class. The experimental class uses a realistic mathematical approach while the control class uses conventional learning and both classes are given material on a system of two-variable linear equations. Analysis after being given treatment shows that both samples are normally distributed and homogeneous. The hypothesis test shows the results of t_count 4.3633> t_table 1.6883, it can be concluded that the level of students' mathematical problem solving ability in the experimental class is better than that of the control class students. For how much influence is carried out using the effect size test which shows the value of d = 1.4 so that it is known that the effect of a realistic mathematical approach on students' mathematical problem solving abilities is 91.9%. This can prove the hypothesis that the mathematical problem solving abilities of students taught by a realistic mathematics approach are better than the problem solving abilities taught by conventional learning.